Bridging intellect and character - Razak, Dzulkifli Abd (2011)
I COULD not wait to get a copy of A Doctor in the House, the memoirs of Tun Dr Mahathir Mohamad.The title implies solutions, as the good doctor prescribed, to be found in some 60 chapters. Plus, you can choose the chapter which you prefer to consult first.Though some information sound familiar due to the author's adamant stance even until today, it provides the context of how and why things were done in certain ways.And this is often missing in other memoirs, leaving many clueless about how decisions were made, rightly or wrongly! One thing that cannot be disputed is when the writer expressed that "education should not only be about acquiring knowledge".